DOES TAX AMNESTY IMPROVE TAX COMPLIANCE AND TAX REVENUE? - Cahyadi, Rony Uncok (Universitas Riau Kepulauan, 2025)
Tax amnesty is an economic mechanism to improve the tax compliance and tax revenue. For that reason, the purpose of this research is to ensures the truth of the statemement, by examines the effect of tax amnesty to tax compliance and tax revenue. Tax amnesty which is examined in this research as the independent variable, while the dependent variable is tax compliance and tax revenue. The data sample used in this research is data that collect from financial statements of Directorat General of Taxes, for the year of 2015-2022. The analyze method in this research using quantitative method. To examines the effect of tax amnesty to tax compliance and tax revenue, this research using a comparison of data variables during the research period and also using multiple linear regression model analysis. The results of this research using both method, found that tax amnesty has positive correlation, but not significant to improving the tax compliance and tax revenue. The result of examine the effect of tax amnesty to tax compliance and tax revenue in this research not match the expected result, that is the tax amnesty was not able to improve tax compliance and tax revenue.